2001
DOI: 10.1074/jbc.m105793200
|View full text |Cite
|
Sign up to set email alerts
|

Function of YidC for the Insertion of M13 Procoat Protein inEscherichia coli

Abstract: The membrane insertion of the Sec-independent M13 Procoat protein in bacteria requires the membrane electrochemical potential and the integral membrane protein YidC. We show here that YidC is involved in the translocation but not in the targeting of the Procoat protein, because we found the protein was partitioned into the membrane in the absence of YidC. YidC can function also to promote membrane insertion of Procoat mutants that insert independently of the membrane potential, proving that the effect of YidC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 46 publications
3
55
0
1
Order By: Relevance
“…On the basis of cross-linking studies, it has been suggested that YidC interacts with nascent TMS, whereas a YidC defect in vivo seems to cause a pleiotropic effect on protein translocation, probably because of jamming of the translocase (14,42,43). It has been postulated that YidC catalyzes the lateral transfer of TMS from the translocase into the lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of cross-linking studies, it has been suggested that YidC interacts with nascent TMS, whereas a YidC defect in vivo seems to cause a pleiotropic effect on protein translocation, probably because of jamming of the translocase (14,42,43). It has been postulated that YidC catalyzes the lateral transfer of TMS from the translocase into the lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are believed to serve as membrane-localized chaperones involved in translocation and assembly of a large number of membrane proteins (23,24) and function in concert with the Sec translocon (23,25,26), as well as independently (27,28). Recently, Oxa2 was identified in mitochondria of Neurospora crassa and functionally complemented the related yeast protein Cox18 (29).…”
mentioning
confidence: 99%
“…Escherichia coli YidC is an abundant membrane protein, with ϳ2500 copies per cell (1) and it is involved in the insertion, folding and/or assembly of membrane proteins into the cytoplasmic membrane independently or in concert with the SecYEG translocon (4). E. coli YidC is essential for cell viability (5) and has been shown to function as an insertase in the membrane insertion of the filamentous phage Pf3 coat and M13 pro-coat proteins (5,6) and the endogenous substrates F 0 c (7), MscL (8,9), and TssL (10). In cooperation with the Sec translocase, YidC assists in the membrane insertion of CyoA (11,12), NuoK (13), and F 0 a and F 0 b subunits of F 1 F 0 ATPase (14), and the translocation of the periplasmic loop 1 and loop 2 of TatC (15).…”
mentioning
confidence: 99%